Diversity of Insect Sesquiterpenoid Regulation - Tsang, Stacey S. K.; Law, Sean T. S.; Li, Chade; Qu, Zhe; Bendena, William G.; Tobe, Stephen S.; Hui, Jerome H. L. (Frontiers in Genetics, 2020)
Insects are arguably the most successful group of animals in the world in terms of both species numbers and diverse habitats. The sesquiterpenoids juvenile hormone, methyl farnesoate and farnesoic acid are well known to regulate metamorphosis, reproduction, sexual dimorphism, eusociality, and defense in insects. Nevertheless, different insects have evolved with different sesquiterpenoid biosynthetic pathway as well as products. On the other hand, noncoding RNAs such as microRNAs have been implicated in regulation of many important biological processes, and have recently been explored in the regulation of sesquiterpenoid production. In this review, we summarise the latest findings on the diversity of sesquiterpenoids reported in different groups of insects, as well as the recent advancements in the understanding of regulation of sesquiterpenoid production by microRNAs.